Efficiency and improvement potential of Sharia insurance: Implications of the financial sector strengthening law - Sunarmo, Sunarmo; Widuhung, Sisca Debyola; Arsyad, Aisyah Tiar; Nasywaa, Nasywaa (Jurnal Ekonomi & Keuangan Islam, 2026)
Purpose – To compare efficiency conditions and potential improvements in the Sharia insurance company and examine its consistency with the law on strengthening and developing the financial sector.Methodology – The research sample included 21 Sharia life and 20 general insurance companies. The secondary data used were sourced from the financial statements of Sharia insurance companies registered with the Financial Services Authority (OJK) and the Indonesian Sharia Insurance Association (AASI) for 2017–2023. The research method used a Data Envelopment Analysis (DEA) approach.Findings – Sharia life insurance in Indonesia shows inefficient conditions, reflected in the low ratio of output to input due to the lack of business income, investment, and tabarru funds. In contrast, the general segment of Sharia was relatively more efficient, but burdened by high assets, liabilities, claims, and operational costs. The potential for improvement towards efficiency could be achieved by optimizing business income and Tabarru funds, as well as controlling inputs proportional to output. The Development and Strengthening of the Financial Sector Law (PPSK Law) policy played a strategic role in strengthening capital and implementing the Sharia unit spin-off obligations expected to form a more independent and competitive institutional structure.Implications – The results have policy implications for regulators and industry players to strengthen the competitiveness of national Sharia insurance.Originality – This research offers a major novelty, namely, comparing the efficiency performance of life insurance and general Sharia, as well as linking efficiency results and potential improvements with the implementation of the PPSK Law.